2006
DOI: 10.1542/peds.2006-2284
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Elevated Lead Levels in Childhood and Pregnancy: An Updated Summary of Evidence for the US Preventive Services Task Force

Abstract: There is no persuasive evidence that screening for elevated lead levels in asymptomatic children will improve clinical outcomes. For those children who are screened and found to have elevated levels, there is conflicting evidence demonstrating the clinical effectiveness of early detection and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…Previous studies in this area have shown that the DMSA has a notable specificity to lead in humans. In addition, a clinical trial has evidenced that this antidote is able to induce a shortterm reduction of blood levels in children exposed to lead, but there was no evidence of it being beneficial on health outcome (Rischitelli et al, 2006).…”
Section: Dmsa -Succimermentioning
confidence: 99%
“…Previous studies in this area have shown that the DMSA has a notable specificity to lead in humans. In addition, a clinical trial has evidenced that this antidote is able to induce a shortterm reduction of blood levels in children exposed to lead, but there was no evidence of it being beneficial on health outcome (Rischitelli et al, 2006).…”
Section: Dmsa -Succimermentioning
confidence: 99%
“…A 2006 United States Preventative Services Task Force concluded that there was no persuasive evidence that screening asymptomatic children would lead to improved clinical outcomes. 25 Yet there continues to be increasing evidence of the negative health outcomes associated with BLLs <10 mg/dL solidifying for many that there is no safe BLL and reinforcing the importance appropriate screening methods and guidelines. [26][27][28][29] Although targeted screening strategies have been developed, 30,31 they have been employed with limited success.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical testing for blood lead levels (BLL) in the region is sporadic, despite calls from experts over the past decade to increase BLL testing and test data sharing (Keyser et al, 2006 (Hopey, 2017b;Rischitelli et al, 2006). Lead testing does not reveal the source of lead contamination (e.g., water, paint, soil), but can help to direct mitigation efforts via targeted assessments in residences of children with high BLL and prioritizing lead remediation resources for those households.…”
Section: Why Has Lead In Water Re-emerged As An Urgent Policy Concern?mentioning
confidence: 99%